ASPEK GEOHIDROLOGI DALAM PENENTUAN LOKASI TAPAK TEMPAT PEMBUANGAN AKHIR SAMPAH (TPA) - Wibowo, Mardi (Jurnal Hidrosfir Indonesia, 2008)
Final Waste Disposal Facilities (FWDF) often pollute the environment,especially in city that have limited area. Groundwater pollution is one of negative impact that is caused FWDF. For minimized the environmental pollution, FWDF should located at area that geologically appropriate. Regional feasibility analysis for FWDF especially from geohydrological aspect is the best first selection step for determine location of FWDF. Geohydrologival aspect include lithology, groundwater water table, slope, rainfall intensity, distance to river, distance to shoreline, distance to fault, volcano eruption, flood and conservation zone.